2022
DOI: 10.1021/acsami.1c24696
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Modulation in Nonlinear Optical Effect in Two-Dimensional van der Waals Cu2MoS4

Abstract: Owing to different nonlinear optical (NLO) motifs with diverse structural and symmetrical assemblies, two-dimensional (2D) van der Waals (vdW) transition metal ternary chalcogenides (TMTCs) have unique advantages in nano-NLO modulation compared to 2D vdW transition metal dichalcogenides (e.g., MoS2). Based on first-principles calculations, in this study, we discover that layered Cu2MoS4 with two tetrahedral [MoS4] and [CuS4] motifs, as a representative 2D vdW TMTC, has an extremely rare sliding-modulated secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Other materials, such as ternary layered compounds, e.g. SnP 2 S 6 , [ 142 ] Nb 3 SeI 7 , [ 199 ] NbOI 2 , [ 84 ] Cu 2 MoS 4 , [ 200 ] and quaternary layered chalcogenides, e.g. CuInP 2 S 6 , [ 83,141 ] AgInP 2 S 6 , [ 201 ] have exhibited strong SHG response due to their intrinsic noncentrosymmetric structures.…”
Section: Fundamentals Of Shg and 2dlmsmentioning
confidence: 99%
“…Other materials, such as ternary layered compounds, e.g. SnP 2 S 6 , [ 142 ] Nb 3 SeI 7 , [ 199 ] NbOI 2 , [ 84 ] Cu 2 MoS 4 , [ 200 ] and quaternary layered chalcogenides, e.g. CuInP 2 S 6 , [ 83,141 ] AgInP 2 S 6 , [ 201 ] have exhibited strong SHG response due to their intrinsic noncentrosymmetric structures.…”
Section: Fundamentals Of Shg and 2dlmsmentioning
confidence: 99%
“…[1][2][3][4][5] Cu 2 MoS 4 belongs to transition metal sulfides with a twodimensional layered stacking structure and differs from other layered materials with hexagonal structure, showing a special tetragonal structure. [6][7][8] Lin and Gan et al 9,10 demonstrated that Cu 2 MoS 4 has electrons confined to Mo atoms and holes confined to Cu and S atoms, and Cu atoms, contributing off-domain s-electrons, have little effect on the band gap width. Due to its unique physicochemical properties, suitable band gap structure and elemental abundance, this material has great potential advantages in the field of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…For bilayer structures, van der Waals sliding will change the lattice pattern and break the symmetry, thereby modulating the electrical, optical and magnetic properties of 2D materials. [5][6][7] Experimentally, Yasuda et al demonstrated an out-of-plane ferroelectric polarization in staggered bilayer h-BN, 8 which is switchable by sliding one layer with respect to the other layer. The switching of electrical polarization is usually driven by the external forces, for example an external electric field.…”
Section: Introductionmentioning
confidence: 99%